The Challenges of Handling Neovascular Glaucoma at Undaan Eye Hospital Surabaya, Indonesia - Malika, Rosalia Adriani; Nuradianti, Lydia (Vision Science and Eye Health Journal, 2023)
Introduction: Neovascular glaucoma (NVG) is a secondary glaucoma, frequently incurable, and can cause blindness. It is characterized by neovascularization over the iris, IOP elevation, and glaucomatous optic neuropathy. Retinal ischemia, which supplies the release of angiogenesis factors, is the leading factor of NVG. Anti-vascular endothelial growth factor (Anti-VEGF) agents are effective at iris and iridocorneal angle neovascularization. Furthermore, laser and surgery are still necessary to decrease intraocular pressure in the condition with ineffective medication. Delay in treatment can lead to sight-threatening glaucoma. Purpose: This study aimed to provide an overview of the incidence and management of NVG at Undaan Eye Hospital, Surabaya, Indonesia. Methods: This descriptive epidemiology study comprised 111 eyes of 102 patients. The inclusion criteria were patients diagnosed with NVG who came to Undaan Eye Hospital for one year (January 2021 to December 2021). Patients with incomplete medical records were excluded. The patient's age, gender, risk factors, and treatment were reviewed. Results: There were 102 patients (111 eyes) diagnosed with NVG. The patients were primarily men (53.2%), and the mean age was 54.98 ± 12.4 years. Diabetes mellitus (DM) was observed in 70 (63.1%) eyes, hypertension in 60 (54.1%) eyes, central retinal vein occlusion (CRVO) in 11 (9.9%) eyes, cholesterol in seven (6.3%) eyes, and branch retinal vein occlusion (BRVO) in one (0,9%) eye. The mean IOP at the time of diagnosis was 42.8 ± 11.2 mmHg. Anti-VEGF (25.2%), trabeculectomy (59.5%), glaucoma drainage device (17.1%), micropulse transscleral cyclophotocoagulation (5.4%) were done as an option of the treatment. Conclusions: NVG is more common in men. Most patients presenting NVG had DM and hypertension with a mean IOP of 42.8 mmHg. Trabeculectomy is the most commonly performed procedure.